Analysis of Factors Affecting Foreign Debt in Indonesia (Case Study 1990-2023) - Prasetyo, Agung; Pasaribu , Esti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the factors that influence foreign debt by using data on foreign exchange reserves, exchange rates, and interest rates on Indonesia's foreign debt for the period 1990-2023. The data used in this research was obtained from the official websites of the Ministry of Finance of Indonesia, the Central Bureau of Statistics (BPS), and Bank Indonesia. This research uses multiple linear regression analysis. The results of this research show that foreign exchange reserves, exchange rates, and interest rates simultaneously influence Indonesia's foreign debt. Partially, foreign exchange reserves have a positive and significant effect on Indonesia's foreign debt, the exchange rate influences Indonesia's foreign debt, and interest rates have a positive effect on Indonesia's foreign debt.